Kesesuaian Lahan Permukiman Pada Kawasan Rawan Bencana Tanah Longsor Di Kabupaten Temanggung - Heru Christanto Hasibuan; Sri Rahayu (Jurusan Perencanaan Wilayah dan Kota, 2017)
The geographical conditions of Indonesia were formed by the three major tectonic plates of the earth that are, the plate of Indo-Australian, Eurasian and Pacific which led to the zone of vulnerable to natural hazard for several regions in Indonesia. Temanggung Regency is one of the regions that were in the zone of vulnerable to natural hazard. Its bumpy topographical condition is starting from the flattened topography at 0-8% up to the steepness more than 40%, which causing the existence of landslide hazard area. Over the last 5 years, Temanggung Regency had suffered at least nine cases of landslide which resulting the loss of life and the material losses in a wide range. Besides was backgrounded by the natural physical condition, it is also triggered by human activity in utilizing the land which does not fit to its designation, especially on the land use settlement. Therefore, an evaluation toward the land use settlement to the landslide-disaster hazard sector in Temanggung Regency will be conducted in this study. From the result of analysis shows that the land use settlement in Temanggung Regency not entirely as it should be, as set out in laws and regulations. Because in its development from 2011 to 2015 was found the comprehensive accretion of land use settlement on the landslide hazard area, especially on the high level and very high level.